Anode‐Free Lithium–Sulfur Cells Enabled by Rationally Tuning Lithium Polysulfide Molecules. (21st July 2022) - Ren, Yuxun; Bhargav, Amruth; Shin, Woochul; Sul, Hyunki; Manthiram, Arumugam
Abstract: The two major barriers of practical lithium–sulfur batteries are the poor reversibility of lithium‐metal anode and sluggish kinetics of sulfur cathode. Here, we report a simple yet cogent, molecular tailoring approach for lithium polysulfides, enabling a synergistic enhancement of anode reversibility and cathode kinetics. We show that SnI4 coordinates with lithium polysulfides to form soluble complexes, resulting in a Li2 SnS3 ‐rich anode interphase layer. As Li2 SnS3 is stable against parasitic reactions and has a lower ionic resistance over cycling, the Li plating/stripping efficiency is greatly improved. In addition, the formation of soluble complexes between SnI4 and lithium polysulfides play a non‐negligible role in suppressing the clustering behavior of lithium polysulfide molecules, resulting in a significant enhancement in sulfur conversion kinetics under lean electrolyte conditions. The synergistic improvement is validated in anode‐free, lean‐electrolyte pouch cells with a Li2 S cathode that displays capacity retention of 78 % after 100 cycles. Abstract : A complexation reaction between metal iodide and lithium polysulfides in the electrolyte enables an effective stabilization of the anode with enhanced sulfur utilization in anode‐free lithium–sulfur cells with lithium sulfide cathode.